PSVII-29 Interests and Values of Dairy Producers and Consumers on Animal Welfare and Sustainability in Southern Brazil. (7th December 2018) - De Paula Vieira, A; Anthony, R; Zanin, E; Barros, C; Fregonesi, J
Abstract: Brazilian consumers and producers' attitudes towards animal welfare and sustainability are surveyed to help the dairy production sector minimize risks. The research informs the: a) Transition from less welfare conventional models to ones that take into consideration consumer concerns and values, economic interests, opportunity for infrastructure development, avenues of information exchange and the value of government or corporate incentive programs; b) Dissemination of reliable information to consumers about the nature of their dairy system and the commodities produced; and c) Development of more effective channels of communication between consumers and other actors in the production and distribution chain. The Methods include analyzing, documenting and comparing the attitudes of Brazilian dairy consumers and farmers towards animal welfare and sustainability concepts applied to dairy systems of high and low external inputs. Interviews and follow up focus groups gauging producers and consumers' attitudes and preferences towards animal welfare and sustainability concepts applied to dairy production using the SAFA framework (FAO, 2013) was employed. Informed by distribution data provided by IBGE (2013), respondents consisted of consumers and farmers in Rio Grande do Sul, Santa Catarina and Parana, important dairy states in Southern Brazil. The Results explore knowledge gaps between respondent groups regarding animal welfare and sustainability concepts and practices and form the basis of recommendations for producers to better aggregate their production quality and compete effectively in light of new marketing requirements and evolving consumer demand for dairy produced according to animal welfare and sustainability indices; and facilitate future studies on validating local and scientific indicators of animal welfare and sustainability on farms. As Conclusion, preliminary data reveals tools for improving how producers communicate about animal welfare and link human and animal quality of life issues to sustainability, economic profitability, environmental protection, technological innovation, and a broader range of socio-cultural aspirations.